Flow based valve position control using NI my DAQ - Dusarlapudi, Kalyan; Uday Kiran, K; V.Narayana, M; Venkata Suman, M (International Journal of Engineering and Technology, 2018)
This paper emphasizes the required valve position by servo mechanism, which decides the flow rate through pipe. The servo position is decided through Ni Lab View virtual indicator& the same position is tracked by potentiometer with NI My DAQ. The deviation of the valve position is finding by comparing both the positions. This study will helps to maintain the desired flow value where flow rate plays an important role such as Pharmaceutical industry, bottle filling industry Etc.Â Â